2014
DOI: 10.1177/0093650214534974
|View full text |Cite
|
Sign up to set email alerts
|

Does Training Improve the Detection of Deception? A Meta-Analysis

Abstract: This meta-analysis examined whether training improves detection of deception.Overall, 30 studies (22 published and 8 unpublished; control-group design) resulted in a small to medium training effect for detection accuracy (k = 30, g u = 0.331) and for lie accuracy (k = 11, g u = 0.422), but not for truth accuracy (k = 11, g u = 0.060). If participants were guided by cues to detect the truth, rather than to detect deception, only truth accuracy was increased. Moderator analyses revealed larger training effects i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
132
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(138 citation statements)
references
References 108 publications
5
132
0
1
Order By: Relevance
“…The finding that this relation was limited to the truthful statements can most likely be explained by the fact that the verbal cues we included in our questionnaire are primarily truth indicators. This correlation might also explain why lie-detection training that focuses primarily on shifting attention from nonverbal to verbal cues is more successful than training that focus on nonverbal, paraverbal, or multichannel cues (Hauch, Sporer, Michael, & Meissner, 2014). When people attend to verbal cues to detect deception, their subjective (i.e., cues they think they use) and objective (i.e., cues they actually use) indicators are more similar.…”
Section: Discussionmentioning
confidence: 99%
“…The finding that this relation was limited to the truthful statements can most likely be explained by the fact that the verbal cues we included in our questionnaire are primarily truth indicators. This correlation might also explain why lie-detection training that focuses primarily on shifting attention from nonverbal to verbal cues is more successful than training that focus on nonverbal, paraverbal, or multichannel cues (Hauch, Sporer, Michael, & Meissner, 2014). When people attend to verbal cues to detect deception, their subjective (i.e., cues they think they use) and objective (i.e., cues they actually use) indicators are more similar.…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta-analyses have found that feedback moderately improves deception detection (Hedge's g = 0.19; Hauch et al 2014), and that feedback across a range of domains can substantially affect performance (Cohen's d = 0.41, Kluger and DeNisi 1996). Critically, specific feedback, such as what a person does right or wrong when forming impressions, has a more meaningful influence than stating whether that person was simply correct or not (Hauch et al 2014). Formal training can therefore increase perceivers' accuracy in specific situations.…”
Section: Introductionmentioning
confidence: 99%
“…Training and feedback are also required to internalize relevant cues that modify the formation of first impressions and improve accuracy (Blanch-Hartigan et al 2012). Previous meta-analyses have found that feedback moderately improves deception detection (Hedge's g = 0.19; Hauch et al 2014), and that feedback across a range of domains can substantially affect performance (Cohen's d = 0.41, Kluger and DeNisi 1996). Critically, specific feedback, such as what a person does right or wrong when forming impressions, has a more meaningful influence than stating whether that person was simply correct or not (Hauch et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This Adaptive Lie Detector People have little idea of when they are being lied to, with accuracy rates only marginally above chance (Bond & DePaulo, 2006;Kraut, 1980). They seem to have the wrong beliefs about what cues give away liars (The Global Deception Research Team, 2006), and even with training there is only a modest increase in accuracy (Frank & Feeley, 2003;Hauch, Sporer, Michael & Meissner, 2014). What is more, there is a robust bias to take what others say at face value and believe it is the truth, dubbed the 'truth bias' (Bond & DePaulo, 2006;McCornack & Parks, 1986), which some have taken as evidence that people are gullible (Buller & Burgoon, 1996;O'Sullivan, 2003) and not in control of this bias (Gilbert, 1991).…”
mentioning
confidence: 99%